PENGEMBANGAN MODUL TERAPI PERMAINAN TRADISIONAL CONGKLAK, ULA SONDA DAN KETIK KUDA UNTUK MENINGKATKAN KETERAMPILAN SOSIAL SISWA - Raden Poppy Shafira Angelia; Zulfan Saam; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to develop a traditional game therapy module of congklak, ula, sonda and horse type to improve students' social skills. The type of research used is Research and Development (R&D) which is limited by several stages. In order to develop a better module in this study, validation tests were carried out by the validator. The data collection technique in this study used a validation questionnaire. The results of this study are that the traditional game therapy modules of congklak, ula, sonda, and horse type have been compiled to improve students' social skills which are divided into 5 guidance activities with a total reading duration± 40 minutes. The result of the module validation test as a whole based on the validator aspect shows that the assessment obtained an average value of 69.92% declared "Good" tested as a guidance medium.Key Words: Module, Traditional Game Therapy, Improve Social Skills